Study of the mass balance, biotransformation and safety of [14C]SHR8554, a novel μ-opioid receptor injection, in healthy Chinese subjects - Shi, Rupeng; Chai, Yi; Feng, Hao; Xie, Lijun; Zhang, Lulu; Zhong, Tianqi; Chen, Juan; Yan, Peng; Zhu, Bei; Zhao, Jun; Zhou, Chen (Frontiers in Pharmacology, 2023)
BACKGROUND: SHR8554 is a novel μ-opioid receptor-biased agonist. It has analgesic effects by selectively activating the G protein-coupled pathway. Additionally, it can weakly activate the β-arrestin-2 pathway, resulting in a limited number of side effects, such as gastrointestinal inhibition. Previous studies have shown that SHR8554 has good analgesic effects, safety and tolerability, but the pharmacokinetic characteristics of SHR8554 in humans have not been reported. This study was designed to investigate the pharmacokinetics and safety of SHR8554 in healthy Chinese male subjects.A single 1 mg/41.3 μCi intravenous dose of [ 14 C]SHR8554 was administered to six healthy male subjects. Blood, urine and faecal samples were collected at continuous time points to analyse SHR8554 parent drug levels and their metabolites. The total radioactivity in blood, plasma, urine and faeces was detected by using a liquid scintillation counter. The dynamic changes of SHR8554 and its metabolite concentration were by liquid chromatography-tandem mass spectrometry (LC/MS), and then pharmacokinetic analysis. The safety of the drug on the subjects was also observed after a single intravenous injection.The total recovery of radioactivity in urine and faeces was 99.68%±0.79% in 216 h, including 76.22%±1.12% in urine and 23.46%±1.36% in faeces. Seventeen major metabolites in blood, urine and faeces were analysed and identified. The main metabolic pathways of SHR8554 in the human body involve 1) N-dealkylation; 2) Odeethylation; 3) mono-oxidation; 4) glucuronidation, etc. The primary mechanism of SHR8554 clearance in the human body is through urinary excretion, primarily in its parent drug and metabolite forms. The drug has good safety, and no serious adverse effects were observed.CONCLUSION: SHR8554 showed favourable pharmacokinetic characteristics and safety profiles in this study. SHR8554 is extensively metabolized in human body. The 3 main metabolic pathways include N-dealkylation and O-deethylation, as well as monooxidation and glucuronidation. The main excretion route of SHR8554 and its metabolites is through urine.